(3EMcGe GdeYQha ef CMcGe GdXQhas - (3YHO GdSdGe Hf GdWjH Hf eMeO GdbGOQj GdMSfj GdeZQHj GdaGSj, CHh eMeO,J (B1110 (3g` s
(3ChdgG (B:s
(3gPG EMcGe GdeYQha ef CMcGe GdXQha CYde Cf GdcdGe Ydi GdXQa jfMUQ aj LgGJ KdGK, aj MOg hCbSGeg hYGedg s
(3BNQgG (B:s
(3hdPdc CWdb GdfMhjhf Ydjg hMOg, hYdjg hYdi GdXQa GSe GdXQa, hNUhUkG EPG PcQ hgeG aj ebGHdI GdLed hgPG BNQ GdcdGe Ydi eG jJYdb HGdXQha s
(3fSNI ajgG VHWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B5 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B225s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B9 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI (B- (3GdQHGW (B(310 (3O(B) s
Keywords: (3GdfMhs